2019
DOI: 10.1063/1.5070080
|View full text |Cite
|
Sign up to set email alerts
|

The positive mass theorem with angular momentum and charge for manifolds with boundary

Abstract: Motivated by the cosmic censorship conjecture in mathematical relativity, we establish the precise mass lower bound for an asymptotically flat Riemannian 3-manifold with nonnegative scalar curvature and minimal surface boundary, in terms of angular momentum and charge. In particular this result does not require the restrictive assumptions of simple connectivity and completeness, which are undesirable from both a mathematical and physical perspective.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…We mention this result does not contradict the results found in [13,14] as in addition to the weak energy condition, the authors again assume maximality. Also, a lower bound for the ADM energy, independent of any energy conditions, was recently obtained in [15].…”
Section: The Positive Mass Theoremsupporting
confidence: 74%
“…We mention this result does not contradict the results found in [13,14] as in addition to the weak energy condition, the authors again assume maximality. Also, a lower bound for the ADM energy, independent of any energy conditions, was recently obtained in [15].…”
Section: The Positive Mass Theoremsupporting
confidence: 74%
“…It should be pointed out that the hypotheses used in Theorem 2.3 is strong, but it is necessary to address the rigidity cases. In general, we remove simple connectivity and completeness for non-smooth initial data sets in three and four dimensions and prove strict inequalities which are generalization of [9]. (b) If M 4 is spin, π 1 pΣ min q " 0, and H 2 pM 4 zW q " 0, where BW " BM n Y Σ min , then the strict inequality in Theorem 2.3-(b) holds.. (c) If M 4 is spin, E " B " 0, π 1 pΣ min q " Z, H 2 pM 4 zW q " Z and J 1 ě J 2 , then the strict inequality in Theorem 2.3-(c) holds.…”
Section: Statement Of Main Resultsmentioning
confidence: 99%
“…This shows that the simple connectivity and two ends assumptions in above inequalities are only technical restriction and not physical features of black holes. Therefore, recently, Khuri, Bryden, and Sokolowsky [9] showed that the strict inequality of (1.2) is true for initial data sets with minimal axially symmetric boundary BM 3 without simple connectivity assumption.…”
Section: Introductionmentioning
confidence: 99%
“…Proof. The following argument is a generalization of that in [8] for outermost minimal surfaces in axisymmetry. Suppose that the outermost apparent horizon Σ does not admit the stated symmetry.…”
Section: Manifolds With Spherical Symmetrymentioning
confidence: 97%